Bases of preparation of public instructors of physical culture in China - Лань [Yu Lan] Юй (Slobozhanskyi Herald of Science and Sport, 2012)
In the article the results of analysis of the system of preparation of public instructors of physical culture in China are given. It was succeeded during research to set, that in accordance with programmatic-normative documents the courses of preparation of public instructors upon termination of those are awarded an instructor state (highest), first, second and third categories and given, a certificate, notarized by General state administration on affairs of physical culture the People’s Republic of China. The course of preparation of instructors makes 60 hours for the instructors of state (highest) category, 90 – for the first, 120 – for the second, 150 – for the third category. The number of instructors in China in 2008 made 650 000 persons, 35 260 from which are graduates of Center of preparation of public instructors in Province Khebey